2008
DOI: 10.1016/j.cub.2008.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Monoamine Oxidase A by Circadian-Clock Components Implies Clock Influence on Mood

Abstract: The circadian clock has been implicated in addiction and several forms of depression [1, 2], indicating interactions between the circadian and the reward systems in the brain [3-5]. Rewards such as food, sex, and drugs influence this system in part by modulating dopamine neurotransmission in the mesolimbic dopamine reward circuit, including the ventral tegmental area (VTA) and the ventral striatum (NAc). Hence, changes in dopamine levels in these brain areas are proposed to influence mood in humans and mice [6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
346
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 369 publications
(374 citation statements)
references
References 23 publications
25
346
2
1
Order By: Relevance
“…Verkes et al (1996) show that BPD, along with suicide ideation and impulsiveness, was associated with diminished circadian rhythmicity in activity as assessed by actigraphy. That the diurnal variation in mood may be more pronounced in BPD patients than in those with depression and healthy controls was suggested by the study of Cowdry et al (1991) and this observation may be in line with recent insight into how the circadian system may impact on affect (Wirz-Justice 2006; Hampp et al 2008;Golder and Macy 2011). Analysis of the diurnal profile of salivary cortisol in female BPD patients reveals an elevated cortisol response to waking as well as a general upregulation of cortisol levels in BPD (Lieb et al 2004).…”
Section: Circadian Rhythms Bpd and Personalitysupporting
confidence: 56%
“…Verkes et al (1996) show that BPD, along with suicide ideation and impulsiveness, was associated with diminished circadian rhythmicity in activity as assessed by actigraphy. That the diurnal variation in mood may be more pronounced in BPD patients than in those with depression and healthy controls was suggested by the study of Cowdry et al (1991) and this observation may be in line with recent insight into how the circadian system may impact on affect (Wirz-Justice 2006; Hampp et al 2008;Golder and Macy 2011). Analysis of the diurnal profile of salivary cortisol in female BPD patients reveals an elevated cortisol response to waking as well as a general upregulation of cortisol levels in BPD (Lieb et al 2004).…”
Section: Circadian Rhythms Bpd and Personalitysupporting
confidence: 56%
“…Furthermore, these animals display a mania like phenotype similar to that observed in patients with bipolar disorder [87]. A molecular link between the circadian clock mechanism and dopamine metabolism has been established [88]. In mice, the clock proteins BMAL1, NPAS2, and PER2 directly regulate expression levels and activity of monoamine oxidase A, an enzyme important in dopamine degradation, in brain regions relevant for reward and mood related behavior.…”
Section: The Impact Of Clock Genes On Physiologymentioning
confidence: 90%
“…Now, we have reported that monoamine oxidase A (MAOA), a mitochondrial enzyme degrading catecholamines including dopamine, is regulated by components of the circadian clock. 4 Interestingly, this regulation is variable depending on cell type, indicating the presence of cell type specific factors modulating BMAL1/NPAS2 or BMAL1/CLOCK dependent transcription. In the mesolimbic dopaminergic reward circuit, including the ventral tegmental area (VTA) and the ventral striatum/nucleus accumbens (NAc) we found a positive influence of PERIOD 2 (PER2) on transcriptional activation of Maoa using mice mutant in the Per2 gene.…”
mentioning
confidence: 99%